Surgical Emergency Deaths in a Teaching Hospital in Lagos, Nigeria - Akinmokun, Israel; Afolayan, M. O.; Ojo, O. A (Nigerian Journal of Orthopaedics and Trauma, 2019)
Introduction: Surgical emergency is a medical condition for which immediate or urgent surgical intervention is required. This includes acute trauma and other life‑ or limb‑threatening conditions that may cause a loss of life or permanent deformity if surgical interventions are not applied immediately. The accident and emergency (A and E) room is the first point of call for patients with such surgical emergencies. This study is an audit of surgical emergency deaths in the A and E of the Lagos University Teaching Hospital (LUTH). Methodology: This was a retrospective study. It involved analysis of the records of patients who were attended to at the A and E room of LUTH, Idi‑Araba, Lagos state. The period of study was 12 months. Data obtained were analysed using Microsoft Excel 2010 (Microsoft Corporation, Redmond, Washington, USA). Results: The crude mortality rate was 8.3%. The overall male:female ratio was 2:1. The average age at death for both sexes was 46.5 ± 17.5 years. The age ranged from 6 to 87 years. Trauma was the cause of death in 99 cases (52.4%), with a male:female ratio of 5.2:1. Traumatic brain injury was the largest contributor of death overall, with a male:female ratio of 6.6:1. The average age of females who died following trauma was 6 years younger than that of the males. More patients involved in trauma died within 24 h of presentation. The overall average age at death for trauma‑related deaths was 38.9 ± 17.2 years. However, the overall average age at death for malignancy‑related causes was 53.9 ± 13.5 years. The male:female ratio for malignancy as a cause of death was 1:2.3. More deaths occurred within ages 20 and 39 years, accounting for almost half (46.8%) of the total deaths. Breast carcinoma was the major (45.3%) cause of death among the malignancy‑related causes of death, with all but one case occurring in women. Conclusion: Mortality at the surgical department of A and E is still high compared to centres of other Western countries. The general populace needs orientation to reduce risk factors for trauma, especially brain injury. The government also needs to improve facilities available at the trauma centre.